2020
DOI: 10.1371/journal.pmed.1003207
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age and the risk of autism spectrum disorder in Sweden, Finland, and Norway: A cohort study

Abstract: Introduction The complex etiology of autism spectrum disorder (ASD) is still unresolved. Preterm birth (<37 weeks of gestation) and its complications are the leading cause of death of babies in the world, and those who survive often have long-term health problems. Length of gestation, including preterm birth, has been linked to ASD risk, but robust estimates for the whole range of gestational ages (GAs) are lacking. The primary objective of this study was to provide a detailed and robust description of ASD ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 55 publications
(109 reference statements)
4
39
3
Order By: Relevance
“…Most previous studies 4 , 5 , 7 , 9 primarily focused on diagnosis in childhood according to 2 (term or preterm) or 3 (term, preterm, and very preterm) levels of classification regarding gestational age at birth. A few recent studies 18 , 28 , 29 , 30 have evaluated the heterogeneity of long-term neuropsychiatric risk among individuals born beyond 37 gestational weeks, reporting findings consistent with our results showing slightly elevated rates of neuropsychiatric disorders among the early term births. A recent study 14 has demonstrated that early term births born at 37 to 39 weeks might have poorer educational outcomes compared with those born at 39 to 41 weeks of gestation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Most previous studies 4 , 5 , 7 , 9 primarily focused on diagnosis in childhood according to 2 (term or preterm) or 3 (term, preterm, and very preterm) levels of classification regarding gestational age at birth. A few recent studies 18 , 28 , 29 , 30 have evaluated the heterogeneity of long-term neuropsychiatric risk among individuals born beyond 37 gestational weeks, reporting findings consistent with our results showing slightly elevated rates of neuropsychiatric disorders among the early term births. A recent study 14 has demonstrated that early term births born at 37 to 39 weeks might have poorer educational outcomes compared with those born at 39 to 41 weeks of gestation.…”
Section: Discussionsupporting
confidence: 91%
“…There has also been evidence on postterm delivery and mental health disorders. 17 , 18 , 31 However, unlike the Helsinki Birth Cohort Study, 17 , 31 we did not find elevated risks for other disorders associated with prolonged gestation except pervasive development disorders, specifically childhood autism.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The highest postnatal microRNA expression levels were observed in children born prematurely at lower gestational ages and in children born with lower birth weight. These findings may also contribute to the explanation of why preterm-born children with lower birth weight have an increased cardiovascular risk and to the explanation of the increase in cardiovascular risk with the decrease in gestational age at delivery [2,5,[9][10][11]15,19,20,22,23,26,27,29,31,35,39,43,44,51,58,59].…”
Section: Discussionmentioning
confidence: 92%
“…Besides, children and young adults born extremely preterm had significantly altered neuropsychological outcomes (lower general cognitive abilities, visuomotor skills, prospective memory, and aspects of executive functions and language) [32,57,58]. Gestational age of birth, including preterm birth, has also been observed to be associated with the risk of autism spectrum disorders [59].…”
Section: Introductionmentioning
confidence: 99%